Piti Maranggangu (Kawin Tangkap) dalam Perspektif Hukum - Safrin Salam; Rambu Susanti Mila Maramba; Rambu Hada Indah; Pajaru Lombu (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
Sumba Island holds a lot of local wisdom. One of the local wisdom is Piti Maranggangu. Piti Maranggangu is a catch / take in meetings that often occur in public places or public places, such as in traditional markets, places of customs activities (traditional parties), on the street, at home and even planted. The purpose of this study was to find out and understand Piti Maranggangu from the point of view of Customary Law and Law No. 1 of 1974 on marriage. The type of research used is socio-legal research with a research location in Sumba Island, East Nusa Tenggara. The results showed that Piti Mara interfered with a review of the principles of customary law that piti maranggangu practices are recognized in the sumba island community and is a form of honest exogamous mating mating system. Referred to as honest exogamy because the edited woman has been positioned as a surrogate in the clan. While Piti Maranggangu in the perspective of Law No. 1 of 1974 can be concluded that there are 2 (two) conditions violated in the marriage process, namely substantive conditions that there is no consent from the bride, then the age of the edited bride is underage (under 19 years). As a result of violating these substantive conditions, Piti Maranggangu can legally be void by law.